Medical education as cultural transmission - Villa-Loriega, Elnora (Danyag : Journal of Humanities and Social Sciences, 1999)
This paper describes the cultural knowledge acquired by medical students and the methods of cultural transmission. Discussions on acquisition of medical culture and the different avenues by which medical culture is transmitted bring to focus the concept of cultural continuity, cultural discontinuity, and cultural compression. Using ethnographic participant observation, gathering of data was done at the West Visayas State University-College of Medicine in Iloilo.